Modified molecular sieve based on liquid phase mediation and preparation method and application thereof

By using alkaline compounds, fluoride and sodium chloride to prepare modified solutions in molecular sieves for liquid-mediated hydrothermal treatment, the problems of high cost and poor stability in molecular sieve defect control and modification technology are solved, high crystallinity and high adsorption rate are achieved, the process is simplified and the cost is reduced.

CN119873857AActive Publication Date: 2025-04-25SUZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411135799.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-04-25
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

The existing molecular sieve defect control and modification technologies have problems such as high cost, poor stability of the mold release process, complex process, high time cost and low efficiency. Especially when dealing with heavy metal ions in nuclear power plant wastewater, the existing adsorption treatment technology has complex operational processes, high cost, long processing time and large waste generation.

Method used

By using alkaline compounds, fluoride and sodium chloride to prepare a modified solution under specific conditions, the liquid-mediated hydrothermal treatment is carried out to dissolve the silicon-aluminum element at some defective sites, and modify the defective sites through condensation reaction to improve the stability and adsorption rate of the molecular sieve.

Benefits of technology

The high crystallinity and high stability of the molecular sieve are achieved, the defect site is significantly reduced, the adsorption rate is improved, the process is simplified, the cost and energy consumption is reduced, and the problems of poor adsorption stability and high cost in the prior art are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873857A_ABST
    Figure CN119873857A_ABST
Patent Text Reader

Abstract

The invention discloses a modified molecular sieve based on liquid phase mediation and a preparation method and application thereof, and the preparation method comprises the following steps: (1) dissolving an alkaline compound, fluoride and sodium chloride in a solvent to obtain a modified solution; and (2) adding a molecular sieve into the modified solution, and carrying out crystallization treatment by adopting a hydrothermal method to obtain the modified molecular sieve based on liquid phase mediation. The modified solution is prepared by taking the alkaline compound, the fluoride and the sodium chloride as main raw materials and is mixed with the molecular sieve, so that the number of defect sites in the molecular sieve is remarkably reduced, the crystallinity of the molecular sieve is improved, and the adsorption rate of the molecular sieve on metal ions in a heavy metal solution is improved. The modified molecular sieve provided by the invention can maintain the stability and excellent crystallinity even under a high-temperature condition, and effectively solves the problems of poor adsorption stability, short service life and high cost of the existing molecular sieve adsorbent on the market under extreme conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of molecular sieves, and in particular to a liquid-phase-mediated modified molecular sieve and a preparation method and application thereof. Background Art

[0002] Molecular sieves have selective adsorption and catalytic properties due to their unique pore structure. After special process treatment, molecular sieves can have more regular pore structures and fewer crystal defects. High-performance molecular sieves have been introduced into sewage treatment, petrochemicals, fine chemicals and other fields due to their better selective adsorption and catalytic properties, showing good market prospects. However, molecular sieves are affected by the proportion and purity of raw materials during the synthesis process, and usually have certain crystal defects. Improper raw material proportions will lead to uneven crystal growth rate and insufficient connection between crystals, while impurities in the raw materials will lead to irregular molecular sieve structure, low product purity, and blockage of molecular sieve pores.

[0003] In order to meet the demand for high performance of molecular sieves, it is necessary to control and modify the defects of molecular sieves. In industry, templates are usually used for defect control, which guides inorganic precursors to form mesoporous molecular sieves with regular pores around them; another common treatment method is secondary crystallization, mixing the molecular sieve with the modification liquid and hydrothermally crystallizing it again, and moving the defect sites to the crystal surface through condensation reaction to reduce the internal defect sites. However, the current molecular sieve defect control and modification technology still faces some problems. For example, the use of templates is generally costly, and the process of removing the templates can easily lead to the collapse of the molecular sieve crystal structure, resulting in the reintroduction of defects and poor stability of the removal process; the secondary crystallization method usually requires the additional addition of silicon and aluminum sources, and faces problems such as high time cost, complex treatment methods, and low efficiency. These problems greatly limit the efficient application of molecular sieve defect control and modification technology.

[0004] In addition, Cs + With Co 2+ It is the main heavy metal ion in the wastewater of nuclear power plants. Although the adsorption treatment technologies on the market, such as the use of gel balls, resins and other adsorption materials, have achieved certain results, they generally have complex operation procedures, high costs, long treatment time and large amounts of waste, which limit their widespread application. The use of modified molecular sieves for adsorption has been widely studied as a potential solution, such as modified molecular sieves prepared by modification with acids, alkalis, organic modifiers, etc., but the process is complex, the pollution is large, the energy consumption is high, and it cannot be widely used. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a liquid-phase mediated modified molecular sieve and a preparation method and application thereof.

[0006] The above object of the present invention is achieved through the following technical solutions:

[0007] The first aspect of the present invention provides a method for preparing a modified molecular sieve based on liquid phase mediation, comprising the following steps:

[0008] (1) dissolving an alkaline compound, fluoride and sodium chloride in a solvent to obtain a modified solution; the concentration of the alkaline compound in the modified solution is 0.01 to 1.0 mol / L, the concentration of the fluoride is 0.01 to 0.2 mol / L, and the concentration of the sodium chloride is 0.4 to 1.5 mol / L;

[0009] (2) adding the molecular sieve to the modified solution obtained in step (1), and performing a hydrothermal method to perform a crystallization treatment to obtain the liquid-phase mediated modified molecular sieve.

[0010] The present invention dissolves silicon and aluminum elements in some defect sites by liquid-phase mediated treatment under specific conditions. At the same time, the hydroxide ions and fluoride ions in the alkaline modified solution can promote the migration of silicate and aluminum ions in the molecular sieve framework, and modify the defect sites through condensation reaction, so that the original defect sites move to the edge of the crystal, and finally significantly reduce the defect sites in the molecular sieve crystal, and improve the stability of the molecular sieve. In addition, Na in sodium chloride + It can exchange ions with the molecular sieve framework, increase the molecular sieve silicon-aluminum ratio, change the original pore structure of the molecular sieve, and thus improve the adsorption rate of the molecular sieve. This modification method is simple, easy to operate and implement, and can significantly improve the stability and adsorption performance of a variety of molecular sieves.

[0011] Furthermore, in step (1), the alkaline compound is selected from sodium hydroxide and / or potassium hydroxide. The alkaline compound can provide an alkaline environment to dissolve the silicon and aluminum elements in the molecular sieve framework.

[0012] Furthermore, in step (1), the fluoride is selected from one or more of ammonium fluoride, sodium fluoride, aluminum fluoride, and hexafluoroaluminate, preferably ammonium fluoride.

[0013] Furthermore, in step (1), the modified solution also includes a silicon source and / or an aluminum source.

[0014] Furthermore, the concentration of the silicon source and / or aluminum source in the modified solution is 0 to 0.015 mol / L.

[0015] Furthermore, the silicon source is preferably sodium silicate, and the aluminum source is preferably sodium metaaluminate.

[0016] The purpose of additionally adding silicon source and / or aluminum source is to increase the concentration of silicon and aluminum in the modified solution, and under the synergistic effect of hydroxide ions and fluoride ions, further promote the migration of silicate and aluminum ions within the molecular sieve framework, greatly shorten the defect modification time, and improve the modification efficiency.

[0017] Furthermore, in step (1), the solvent is preferably water.

[0018] Furthermore, in step (2), the molecular sieve is an LTA type molecular sieve and / or a FAU type molecular sieve.

[0019] Furthermore, in step (2), the solid-liquid ratio of the molecular sieve to the modified solution is 1 g: (10-50) mL.

[0020] Furthermore, in step (2), the temperature of the crystallization treatment is 90 to 120°C.

[0021] Furthermore, in step (2), the crystallization treatment time is 3 to 9 hours.

[0022] The second aspect of the present invention provides a liquid-phase mediated modified molecular sieve obtained by the preparation method described in the first aspect.

[0023] After the liquid-phase-mediated modified molecular sieve is calcined, its crystallinity can be tested.

[0024] Furthermore, the calcination temperature is 400-1200°C.

[0025] Furthermore, the calcination treatment time is 1 to 5 hours.

[0026] The third aspect of the present invention provides the use of the liquid-phase mediated modified molecular sieve described in the second aspect in metal ion adsorption, which is mainly used for the adsorption of metal ions in heavy metal solutions.

[0027] Furthermore, the metal ion is a cesium ion (Cs + ) and / or cobalt ions (Co 2+ ).

[0028] Furthermore, the concentration of metal ions in the heavy metal solution is 100-1000 mg / L.

[0029] Beneficial effects of the present invention:

[0030] 1. The present invention uses alkaline compounds, fluoride, and sodium chloride as main raw materials to prepare a modified solution. The crystallinity of the molecular sieve after liquid-phase mediated treatment in the modified solution can reach a level of more than 99%, and the crystallinity of the molecular sieve can be basically unchanged under high temperature conditions. On the one hand, the alkaline modified solution can dissolve the silicon and aluminum elements in some defect sites; on the other hand, the hydroxide ions and fluoride ions in the modified solution can promote the migration of silicate and aluminum ions in the molecular sieve framework, respectively, and modify the defect sites through condensation reactions, so that the original defect sites move to the edge of the crystal, and finally significantly reduce the defect sites in the molecular sieve crystal, and improve the stability of the molecular sieve. The Na of sodium chloride in the modified solution + It can undergo ion exchange with the molecular sieve framework to change the molecular sieve pore structure, thereby improving the adsorption rate of the molecular sieve.

[0031] 2. The raw materials of the modified solution in the present invention, namely, alkaline compounds, fluoride and sodium chloride, are cheap and can be reused. The molecular sieve modification process is mild, and compared with the existing molecular sieve modification technology, it not only simplifies the production process, but also reduces production energy consumption and cost.

[0032] 3. The modified molecular sieve provided by the present invention has high crystallinity, large micropore capacity, small number of defect sites, high stability, and can still maintain its stability and excellent crystallinity at high temperatures, effectively solving the problems of poor adsorption stability, short service life and high cost of existing molecular sieve adsorbents on the market under extreme conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is the XRD diagram of the LTA type molecular sieve, the modified LTA type molecular sieve prepared in Example 1 and the modified LTA type molecular sieve prepared in Example 2.

[0034] Figure 2 1 and 2 are XRD diagrams of the FAU type molecular sieve, the modified FAU type molecular sieve prepared in Example 10, and the modified FAU type molecular sieve prepared in Example 11.

[0035] Figure 3 It is a crystallinity data diagram of LTA type molecular sieve and modified LTA type molecular sieve prepared in Example 2 at different temperatures.

[0036] Figure 4 It is a crystallinity data diagram of FAU type molecular sieve and modified FAU type molecular sieve prepared in Example 11 at different temperatures. DETAILED DESCRIPTION

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0038] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0039] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0040] Example 1

[0041] A method for preparing a liquid-phase mediated modified LTA molecular sieve comprises the following steps:

[0042] (1) 0.05 g of sodium hydroxide, 0.0185 g of ammonium fluoride and 1.17 g of sodium chloride were dissolved in 50 mL of deionized water and stirred thoroughly to obtain a modified solution, wherein the concentration of the alkaline compound in the modified solution was 0.025 mol / L, the concentration of the fluoride was 0.01 mol / L, and the concentration of the sodium chloride was 0.4 mol / L.

[0043] (2) Add 10 g of LTA molecular sieve to the modified solution obtained in step (1), and perform crystallization treatment in a polytetrafluoroethylene-lined hydrothermal reactor at 90° C. for 5 h. Ultrasonic treatment of the obtained modified molecular sieve turbid solution for 1 min, centrifuge to separate the solid and liquid, remove the aqueous phase, and place in an oven at 80° C. to dry for 16 h to obtain a modified LTA molecular sieve.

[0044] Example 2

[0045] A method for preparing a liquid-phase mediated modified LTA molecular sieve comprises the following steps:

[0046] (1) 0.012 g of sodium hydroxide, 0.011 g of ammonium fluoride, 0.76 g of sodium chloride and 0.012 g of sodium aluminate were dissolved in 30 mL of deionized water and stirred thoroughly to obtain a modified solution, wherein the concentration of the alkaline compound in the modified solution was 0.01 mol / L, the concentration of the fluoride was 0.01 mol / L, the concentration of the sodium chloride was 0.43 mol / L, and the concentration of the sodium aluminate was 0.0049 mol / L.

[0047] (2) Add 10 g of LTA molecular sieve to the modified solution obtained in step (1), and perform crystallization treatment in a polytetrafluoroethylene-lined hydrothermal reactor at 90° C. for 3 h. Ultrasonic treatment of the obtained modified molecular sieve turbid solution for 1 min, centrifuge to separate the solid and liquid, remove the aqueous phase, and place in an oven at 80° C. to dry for 16 h to obtain a modified LTA molecular sieve.

[0048] Example 3

[0049] A method for preparing a modified LTA molecular sieve based on liquid phase mediation is basically the same as that of Example 2, except that in step (2), the crystallization treatment time is 1 hour.

[0050] Example 4

[0051] A method for preparing a modified LTA type molecular sieve based on liquid phase mediation is basically the same as Example 2, except that in step (2), the crystallization treatment time is 9 hours.

[0052] Example 5

[0053] A method for preparing a modified LTA type molecular sieve based on liquid phase mediation is basically the same as Example 2, except that in step (2), the crystallization treatment time is 18 hours.

[0054] Example 6

[0055] A method for preparing a modified LTA type molecular sieve based on liquid phase mediation is basically the same as Example 2, except that in step (2), the crystallization treatment time is 27 hours.

[0056] Example 7

[0057] A method for preparing a modified LTA type molecular sieve based on liquid phase mediation is basically the same as Example 2, except that in step (2), the temperature of the crystallization treatment is 50°C.

[0058] Example 8

[0059] A method for preparing a modified LTA type molecular sieve based on liquid phase mediation is basically the same as Example 2, except that in step (2), the temperature of the crystallization treatment is 120°C.

[0060] Example 9

[0061] A method for preparing a liquid-phase mediated modified LTA molecular sieve is basically the same as that of Example 2, except that in step (2), the temperature of the crystallization treatment is 180°C.

[0062] Example 10

[0063] A method for preparing a liquid-phase mediated modified FAU molecular sieve comprises the following steps:

[0064] (1) 0.15 g of sodium hydroxide, 0.167 g of ammonium fluoride and 0.72 g of sodium chloride were dissolved in 50 mL of deionized water and stirred thoroughly to obtain a modified solution, wherein the concentration of the alkaline compound in the modified solution was 0.075 mol / L, the concentration of the fluoride was 0.09 mol / L, and the concentration of the sodium chloride was 0.245 mol / L.

[0065] (2) 10 g of FAU molecular sieve was added to the modified solution obtained in step (1), and crystallization treatment was carried out in a polytetrafluoroethylene-lined hydrothermal reactor at 120° C. for 8 h. The modified molecular sieve turbid solution was ultrasonically treated for 1 min, centrifuged to separate the solid and liquid, and then the aqueous phase was removed. The solution was placed in an oven at 80° C. and dried for 16 h to obtain a modified FAU molecular sieve.

[0066] Embodiment 11

[0067] A method for preparing a liquid-phase mediated modified FAU molecular sieve comprises the following steps:

[0068] (1) 0.06 g of sodium hydroxide, 0.1 g of ammonium fluoride, 0.43 g of sodium chloride and 0.0219 g of sodium silicate were dissolved in 30 mL of deionized water and stirred thoroughly to obtain a modified solution, wherein the concentration of the alkaline compound in the modified solution was 0.05 mol / L, the concentration of the fluoride was 0.09 mol / L, the concentration of the sodium chloride was 0.245 mol / L, and the concentration of the sodium silicate was 0.006 mol / L.

[0069] (2) 10 g of FAU molecular sieve was added to the modified solution obtained in step (1), and crystallization treatment was carried out in a polytetrafluoroethylene-lined hydrothermal reactor at 120° C. for 5 h. The modified molecular sieve turbid solution was ultrasonically treated for 1 min, centrifuged to separate the solid and liquid, and then the aqueous phase was removed. The solution was placed in an oven at 80° C. and dried for 16 h to obtain a modified FAU molecular sieve.

[0070] Comparative Example 1

[0071] A method for preparing a modified LTA type molecular sieve is basically the same as that of Example 2, except that in step (1), ammonium fluoride is not added to the modified solution.

[0072] Comparative Example 2

[0073] A method for preparing a modified LTA molecular sieve is basically the same as that of Example 2, except that in step (1), the concentration of ammonium fluoride in the modified solution is 0.4 mol / L.

[0074] Comparative Example 3

[0075] A method for preparing a modified LTA molecular sieve is basically the same as that of Example 2, except that in step (1), no sodium hydroxide is added to the modified solution.

[0076] Comparative Example 4

[0077] A method for preparing a modified LTA molecular sieve is basically the same as that of Example 2, except that in step (1), the concentration of sodium hydroxide in the modified solution is 2.1 mol / L.

[0078] Comparative Example 5

[0079] A method for preparing a modified LTA type molecular sieve is basically the same as that of Example 2, except that in step (1), no sodium chloride is added to the modified solution.

[0080] Comparative Example 6

[0081] A method for preparing a modified LTA molecular sieve is basically the same as that of Example 2, except that in step (1), the concentration of sodium chloride in the modified solution is 2 mol / L.

[0082] Test Example 1

[0083] The crystal structures of the LTA molecular sieve, the modified LTA molecular sieve prepared in Example 1 and the modified LTA molecular sieve prepared in Example 2 were observed by X-ray diffraction (XRD). Figure 1 As shown, the characteristic diffraction peak intensity of the modified LTA molecular sieve is significantly enhanced, indicating that the modified LTA molecular sieve has better crystallinity, and an appropriate amount of sodium aluminate is additionally added in Example 2, which significantly shortens the modification time.

[0084] The crystal structures of the FAU molecular sieve, the modified FAU molecular sieve prepared in Example 10 and the modified FAU molecular sieve prepared in Example 11 were observed by XRD. Figure 2 As shown, the characteristic diffraction peak intensity of the modified FAU molecular sieve is significantly enhanced, indicating that the modified FAU molecular sieve has better crystallinity. In addition, an appropriate amount of sodium silicate is added in Example 11, which significantly shortens the modification time.

[0085] Test Example 2

[0086] The diffraction intensity of the modified molecular sieves of Examples 1 to 11 and Comparative Examples 1 to 6 was tested by an X-ray diffractometer, and the relative crystallinity was calculated. The calculation formula is as follows:

[0087]

[0088] Where X cis the relative crystallinity of the synthesized product, in %; X0 is the crystallinity of the molecular sieve standard sample of this model, in %; I c is the diffraction intensity of a certain crystal plane (hkl) of the synthetic molecular sieve; I0 is the diffraction intensity of a certain crystal plane (hkl) of the standard sample of this model of molecular sieve.

[0089] The relative crystallinity data of the modified LTA molecular sieves prepared in Examples 1 to 2, the modified FAU molecular sieves prepared in Examples 10 to 11, and the modified LTA molecular sieves prepared in Comparative Examples 1 to 6 are shown in Table 1:

[0090] Table 1

[0091]

[0092]

[0093] As can be seen from the data in Table 1, the LTA type and FAU type molecular sieves with silicate as the framework, after being modified by the liquid phase mediated treatment method provided by the present invention, the crystallinity of the molecular sieves is significantly improved. The data of Examples 1 to 2 and Examples 10 to 11 show that when an appropriate amount of silicon source or aluminum source is additionally added to the modified solution, the modification time can be effectively shortened and the modification efficiency can be improved while maintaining the modification effect basically unchanged. By comparing Example 2 with Examples 3 to 9, it can be seen that the temperature of the crystallization treatment is preferably 90 to 120 ° C, and the time of the crystallization treatment is preferably 3 to 9h. In addition, by comparing Example 2 with Comparative Examples 1 to 6, it can be seen that when hydroxide ions and fluoride ions exist alone, they hardly show modification ability. Only when both exist at the same time and are maintained within a certain concentration range can the crystal defects be effectively modified. When the concentration of hydroxide ions or fluoride ions is too high, the dissolution of silicon and aluminum elements in the molecular sieve framework will be accelerated to a certain extent, so that a large number of new lattice defects appear in the molecular sieve, which leads to a significant decrease in crystallinity. In Comparative Example 6, when the sodium chloride concentration is too high, the crystallinity of the molecular sieve decreases, indicating that in the case of excessive sodium ions, the aluminum element in the molecular sieve framework will be excessively dissolved, destroying the molecular sieve framework and reducing the crystallinity.

[0094] Test Example 3

[0095] 1 g of LTA molecular sieve (before modification) and the modified LTA molecular sieve (after modification) prepared in Example 2 were placed in a muffle furnace and calcined at 500°C, 600°C, 700°C, 800°C, 900°C and 1000°C for 3 h, respectively. After cooling, the change in diffraction intensity was tested by an X-ray diffractometer, and the relative crystallinity was calculated. The test results are as follows: Figure 3 shown.

[0096] 1 g of FAU molecular sieve (before modification) and the modified FAU molecular sieve (after modification) prepared in Example 11 were placed in a muffle furnace and calcined at 500° C., 600° C., 700° C., 800° C., 900° C., and 1000° C. for 3 h, respectively. After cooling, the change in diffraction intensity was tested by an X-ray diffractometer, and the relative crystallinity was calculated. The test results are shown in FIG. Figure 4 shown.

[0097] from Figure 3 and Figure 4 It can be seen that no matter it is LTA type zeolite or FAU type zeolite, the critical temperature of crystallinity decrease is significantly improved after modification. Compared with before modification, the crystallinity of the zeolite at the same temperature is improved, which proves that the modification effectively improves the high temperature stability of the zeolite.

[0098] Test Example 4

[0099] The LTA molecular sieve, the modified LTA molecular sieve prepared in Examples 1 to 2, and the modified LTA molecular sieve prepared in Comparative Examples 1 to 6 were activated at 200°C in vacuum for 2h. After cooling, the modified LTA molecular sieve was mixed with a heavy metal solution at a solid-liquid ratio of 1g:100mL and placed in a container. The heavy metal solutions were 100mg / L, 500mg / L, 1000mg / L Cs2CO3 solutions and 100mg / L, 500mg / L, 1000mg / L Co(NO3)2 solutions. The container was fixed on a long-axis mixer and mixed for 9h to allow sufficient adsorption, and then immediately filtered with a PES membrane; the filtrate was then diluted 10,000 times with a 2% dilute nitric acid solution to obtain a sample solution, and the concentration of metal ions in the sample solution was obtained by measuring the sample solution by ICP-OES (or ICP-MS).

[0100] Use the following formula to calculate the metal ion removal efficiency (R) and adsorption capacity Q e (mg / g) and distribution coefficient K d (mL / g).

[0101] The removal efficiency calculation formula is:

[0102]

[0103] The adsorption capacity calculation formula is:

[0104]

[0105] Among them C i and C e are the initial concentration and equilibrium concentration of the heavy metal solution (mg / L), V is the volume of the solution (L), and m is the mass of the adsorbent (g).

[0106] The LTA molecular sieve, the modified LTA molecular sieve prepared in Examples 1 to 2, and the modified LTA molecular sieve prepared in Comparative Examples 1 to 6 were used to purify Cs in a mixed solution of Cs2CO3 and Co(NO3)2 at concentrations of 100 mg / L, 500 mg / L, and 1000 mg / L, respectively. + and Co 2+ The removal rate and adsorption capacity data are shown in Tables 2 to 7:

[0107] Table 2

[0108] <![CDATA[Sample - 100mg / L Cs + > Removal efficiency R(%) <![CDATA[Adsorption capacity Q e (mg / g)]]> LTA molecular sieve 84.1 257.1 Example 1 99.7 357.3 Example 2 99.8 369.2 Comparative Example 1 90.9 305.7 Comparative Example 2 75.2 226.4 Comparative Example 3 85.1 260.5 Comparative Example 4 72.9 220.9 Comparative Example 5 86.4 268.4 Comparative Example 6 85.1 264.8

[0109] Table 3

[0110]

[0111]

[0112] Table 4

[0113] <![CDATA[Sample - 500mg / L Cs + > Removal efficiency R(%) <![CDATA[Adsorption capacity Q e (mg / g)]]> LTA molecular sieve 82.9 250.3 Example 1 98.6 352.3 Example 2 98.2 361.8 Comparative Example 1 88.1 298.5 Comparative Example 2 73.8 221.6 Comparative Example 3 84.3 253.2 Comparative Example 4 71.3 216.1 Comparative Example 5 84.7 260.6 Comparative Example 6 83.5 253.2

[0114] Table 5

[0115]

[0116]

[0117] Table 6

[0118] <![CDATA[Sample - 1000mg / L Cs + > Removal efficiency R(%) <![CDATA[Adsorption capacity Q e (mg / g)]]> LTA molecular sieve 80.7 245.7 Example 1 95.1 347.8 Example 2 95.3 353.2 Comparative Example 1 85.1 288.4 Comparative Example 2 70.6 211.5 Comparative Example 3 80.8 241.8 Comparative Example 4 68.2 202.9 Comparative Example 5 81.4 252.8 Comparative Example 6 80.9 241.3

[0119] Table 7

[0120] <![CDATA[Sample - 1000mg / L Co 2+ > Removal efficiency R(%) <![CDATA[Adsorption capacity Q e (mg / g)]]> LTA molecular sieve 62.4 161.6 Example 1 81.8 228.3 Example 2 84.1 239.3 Comparative Example 1 73.3 193.1 Comparative Example 2 49.9 126.4 Comparative Example 3 60.5 159.8 Comparative Example 4 50.2 123.9 Comparative Example 5 64.4 164.6 Comparative Example 6 74.7 192.7

[0121] From Tables 2 to 7, it can be seen that the modified LTA molecular sieves prepared in Examples 1 to 2 showed good performance on Cs + and Co 2+Higher adsorption rate. In each concentration solution, no fluoride ions were added in Comparative Example 1. Although the adsorption effect of the modified molecular sieve was significantly improved, the lattice defects in the molecular sieve were not effectively repaired, and the molecular sieve crystallinity was not high. In Comparative Example 2, when fluoride ions were excessive, the crystallinity was good, and the modification effect was not significantly improved or even decreased. In Comparative Example 3, when no alkali source was provided, the adsorption rate of the molecular sieve remained almost unchanged, indicating that the effect of hydroxide on the modification was very small. In Comparative Example 4, when the alkali source was excessive, the dissolution rate of silicon and aluminum elements in the molecular sieve framework was greater than the modification rate, a large number of new lattice defects appeared in the molecular sieve, and the adsorption rate also decreased. In Comparative Example 5, when sodium chloride was not added, the modification effect was not obvious. In Comparative Example 6, when sodium chloride was excessively added, the removal efficiency and adsorption capacity of the modified molecular sieve increased, but the increase was not as obvious as the modified LTA molecular sieve prepared in Examples 1 to 2.

[0122] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a modified molecular sieve based on liquid phase mediation, characterized in that: The following steps are involved: (1) dissolving an alkaline compound, fluoride and sodium chloride in a solvent to obtain a modified solution; The concentration of the alkaline compound in the modified solution is 0.01-1.0 mol / L, the concentration of the fluoride is 0.01-0.2 mol / L, and the concentration of the sodium chloride is 0.4-1.5 mol / L; (2) adding the molecular sieve to the modified solution obtained in step (1), and performing a hydrothermal method to perform a crystallization treatment to obtain the liquid-phase mediated modified molecular sieve.

2. The preparation method according to claim 1, characterized in that: In step (1), the alkaline compound is selected from sodium hydroxide and / or potassium hydroxide, and the fluoride is selected from one or more of ammonium fluoride, sodium fluoride, aluminum fluoride, and hexafluoroaluminate.

3. The preparation method according to claim 1, characterized in that: In step (1), the modified solution also includes a silicon source and / or an aluminum source.

4. The preparation method according to claim 1, characterized in that: In step (2), the molecular sieve is an LTA type molecular sieve and / or a FAU type molecular sieve.

5. The preparation method according to claim 1, characterized in that: In step (2), the solid-liquid ratio of the molecular sieve to the modified solution is 1 g: (10-50) mL.

6. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the crystallization treatment is 90-120°C.

7. The preparation method according to claim 1, characterized in that: In step (2), the crystallization treatment time is 3 to 9 hours.

8. The liquid-phase mediated modified molecular sieve obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the liquid-phase mediated modified molecular sieve according to claim 8 in metal ion adsorption.

10. The use according to claim 9, characterized in that: The metal ions are cesium ions and / or cobalt ions.

Citation Information

Patent Citations

  • SCM-9 molecular sieve and preparation method thereof

    CN106830004A

  • Modified A-type molecular sieve as well as preparation method and application thereof

    CN118324154A

  • Rare earth silicate molecular sieves

    US20030049200A1

  • Substitution of Cr in place of Al in the framework of molecular sieve via treatment with fluoride salts

    US5186918A

  • Method of making molecular sieves of con framework type

    WO2024010995A1